2021
DOI: 10.3390/microorganisms9061116
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Conditions Modulate the Transcriptomic Response of Both Caulobacter crescentus Morphotypes to Cu Stress

Abstract: Bacteria encounter elevated copper (Cu) concentrations in multiple environments, varying from mining wastes to antimicrobial applications of copper. As the role of the environment in the bacterial response to Cu ion exposure remains elusive, we used a tagRNA-seq approach to elucidate the disparate responses of two morphotypes of Caulobacter crescentus NA1000 to moderate Cu stress in a complex rich (PYE) medium and a defined poor (M2G) medium. The transcriptome was more responsive in M2G, where we observed an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 125 publications
0
11
0
Order By: Relevance
“…S1B ). These findings are reinforced by the differential expression of genes involved in oxidative stress response upon Cu stress, including those encoding the catalase KatG (CCNA_03138) and the superoxide dismutases SodA (CCNA_03672) and SodB (CCNA_01855) [4]. Together these data argue for the rapid generation of an oxidative stress in SW cells exposed to Cu.…”
Section: Resultsmentioning
confidence: 99%
“…S1B ). These findings are reinforced by the differential expression of genes involved in oxidative stress response upon Cu stress, including those encoding the catalase KatG (CCNA_03138) and the superoxide dismutases SodA (CCNA_03672) and SodB (CCNA_01855) [4]. Together these data argue for the rapid generation of an oxidative stress in SW cells exposed to Cu.…”
Section: Resultsmentioning
confidence: 99%
“…Bufferins are involved in adaptation to copper stress. In C. vibrioides, buf1 and buf2 BGCs belong to the SigF-controlled, core regulon of copper stress 12,14,31 . To test if they could be upregulated by other biologically relevant transition metals, we generated reporter fusions within bufA1 and bufA2 and confirmed that both are induced by Cu 2+ but not Fe 2+ , Zn 2+ or Mn 2+ (Fig.…”
Section: Gig-like Operons Belong To Putative Ripp Bgcsmentioning
confidence: 99%
“…S1). The latter operons are up-regulated upon exposure to transition metals, notably copper [11][12][13][14] . In particular, the C. vibrioides operon is part of the few genes induced by copper in both swarmer and stalked cells 14 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations